Case Report: Histiocytic Necrotizing Lymphadenitis (Kikuchi–Fujimoto Disease) Concurrent With Aseptic Meningitis - Song, Yanna; Liu, Shan; Song, Lei; Chen, Huaqiu; Bai, Miaoshui; Yan, Jinhua; Luo, Tianfei; Liu, Kangding; Sun, Li; Zhao, Yang (Frontiers in Neurology, 2021)
Abstract Kikuchi-Fujimoto disease (KFD), also known as histiocytic necrotizing lymphadenitis, is a rare, benign, self-limiting disease characterized by local lymphadenopathy. Central nervous system involvement in KFD is extremely rare and remains a diagnostic challenge. Only 41 cases of aseptic meningitis associated with KFD have been reported worldwide, and just four (including our case) of KFD with meningitis as the first symptom. We report a case of KFD accompanied by aseptic meningitis with severe high intracranial pressure (400 mm H2O), increased white blood cell count (56×106/L), and moderately elevated protein level (0.52 g/L). This case is unique in the delayed appearance of lymphadenopathy. After 1 month of treatment with steroids, fever, headache, and lymphadenopathy gradually disappeared, and cerebrospinal fluid examination gradually became normal. In conclusion, based on our case findings and our literature review on KFD with aseptic meningitis, a diagnosis of KFD should be considered when delayed appearance of lymphadenopathy is observed in patients with aseptic meningitis.